The Influence of Project-Based Online Learning and Self-Efficacy on Students' Critical Thinking Learning Outcomes - Pujianto, Wahyu Hadi; Degeng, I Nyoman Sudana; Kamdi, Waras; Degeng, Made Duananda Kartika (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Online project-based learning models have become a significant concern in modern education. In physics subjects, understanding motion dynamics requires strong critical thinking skills. The research aims to describe students' critical thinking abilities regarding the concept of using project-based learning online (PJBoL) and face-to-face (PjBL) based on the level of self-efficacy (high, medium, low) and interaction between learning methods and self-efficacy. This research used an experimental design with research subjects in the form of class XI students at SMAN 1 Kesamben. Learning was carried out over six meetings using the same material. The independent variable in this research is the PjBoL model, while the dependent variable is students' critical thinking abilities. Data analysis was done using two-way ANCOVA to evaluate the relationships and interactions between these variables. The research results show a significant difference in students' critical thinking abilities on the concept of dynamics of motion between PJBoL and face-to-face, as well as in students' critical thinking abilities on self-efficacy. It is recommended that the PjBL Model, carried out face-to-face, is suitable for millennial students and has been proven to have better critical thinking learning outcomes.